THE MANAGEMENT STRATEGY OF HEADMASTER IN EFFORTS TO INCREASE SELF AWARENESS OF SCHOOL RESIDENTS OF THE IMPORTANCE ENVIRONMENT - Sholekah, Friska Fitriani; Mahmudah, Fitri Nur (Universitas Pendidikan Indonesia, 2020)
The research aims to discuss(1) How planned of the headmaster in an effort to increase self-awareness of school residents regarding the importance of the environment, 2) How to implement planned programs related to efforts to increase self-awareness of school residents, and 3) identify supporting factors in implementation of the program carried out as an effort to increase self-awareness of school residents. The method of research used qualitative method. Subjects of this research consisted of headmaster, subject teachers, and students. Subjects of research is based on determining purposive random sampling technique. Collecting of data is through interviews, observation and documentation. The analyzing of data using the Miles Huberman analysis model with the several stages are collecting of data, data reduction, data presentation and drawing conclusions. The results show that there an increased in self-awareness of school residents about the environment after several programs had been carried out. The vision, mission and regulation of the school are being the one of programs that succeeded in increase awareness of school residents. The implementation program by applying clean fridays, installing CCTVs and coaching by the headmaster and teachers to the students directly. The supporting factors in implementation of efforts to increase self-awareness of school residents to the environment are the commitment, awareness and desire of school residents to embody the programs that have been implemented. The strategy of headmaster is always monitor the activities of school residents through the CCTVs that have been installed and spot checking directly to be more effective and the results showed increased self-awareness of school residents for enviroment has occurred since last semester.